Assay of Paracetamol in tablet form from different Manufacturing sources in Iraqi market - N. Al-Sabea (College of Pharmacy / Mustansiriyah University, 2011)
Paracetamol (Acetaminophen) is an analgesic, antipyretic used in treatment of fever and pain in adult and children. It can be assayed using HPLC to estimate the weight of the drug in the specific dosage form. In this study we take samples of the Paracetamol (500mg) drug from five different pharmaceutical companies in the Iraqi market to make comparison study of the drug content in these samples. The study carried out by the formation of calibration curve using standard solutions of different concentrations of the external standard paracetamol USP 30, which results in different readings of the area under the peak. The curve will follow straight line equation. The paracetamol was extracted from its tablets & then injected into HPLC system to determine the area under the peak. From the resulted area we can calculate the concentration and the weight by the straight line equation. The results show that all of five samples are within the maximum percentage of the differences allowed according USP from (90% - 110%).